Exploring the impact of childhood maltreatment and BPD on impulsivity in crimes of passion - Jin, Michelle; Wang, Zhongrui; Zhou, Ying; Zhong, Jie (Frontiers in Psychiatry, 2023)
Background Crimes of passion, characterized as unpremeditated impulsive aggression, have garnered increasing attention in recent years. Impulsivity, a major factor in crimes of passion, is also a common feature of various health conditions, including Borderline Personality Disorder (BPD). Childhood maltreatment is considered a significant precursor to BPD and is closely related to impulsivity. Although prior research has affirmed the relationship between impulsivity, childhood maltreatment, BPD, and criminal behavior, few studies have examined these variables’ interconnections within the context of crimes of passion. This study seeks to explore the relationship between childhood maltreatment, BPD, and impulsivity in crimes of passion, assessing the former’s impact on the latter. Method Our research examined 133 crimes of passion offenders and 149 other offenders from the Shenzhen male prison in China. All 282 participants completed The Abbreviated Version of The Barratt Impulsiveness Scale (ABIS), The UPPS Impulsivity Scale (Urgency, Premeditation, Perseverance, Sensation Seeking), The McLean Screening Instrument for Borderline Personality Disorder (MSI-BPD), and The Childhood Trauma Questionnaire (CTQ). Results Our findings indicated that (1) crimes of passion offenders scored significantly higher in emotional neglect, physical neglect, and overall childhood maltreatment than did other offenders, and childhood maltreatment scores were notably higher in the high BPD trait group. (2) Crimes of passion offenders demonstrated significantly elevated impulsivity in attention and nonplanning scales compared to other offenders. Impulsivity scores across all scales were also significantly higher in the high BPD trait group. (3) Emotional neglect was found to significantly influence the urgency scale in crimes of passion offenders. An interaction effect was noted between physical abuse and high BPD traits, leading to increased impulsivity in crimes of passion offenders. Conclusion This study underscores the predictive roles of childhood maltreatment and BPD in determining impulsivity within the context of crimes of passion.